Determination of Indinavir Sulphate by Visible Spectrophotometry - Sarma, C.S.N.; Kamala Sastri, C.; Sastri, C.S.P. (Asian Journal of Chemistry, 2010)
Three simple and sensitive visible spectrophotometric methods (M1, M2, M3) are developed for the estimation of Indinavir sulphate (INS) in bulk and dosage forms. They are based on the formation of coloured species with sodium nitroprusside-acetaldehyde (SNP-ACD, method-M1), cobalt thiocyanate (CTC, method-M2) and citric acid-acetic anhydride (CA-AA, method-M3) reagents exhibiting maximum absorption at 560, 600, and 560 nm respectively. Methods M1, M2, M3 obeyed Beer's law limits 0.6–6 μg mL–1, 1.4–15 μg mL–1 and 1.65–20 μg mL–1 repectively and are statistically validated. The proposed methods are selective, simple and economicical for the quantitative determination of Indinavir sulphate.